2013
DOI: 10.4103/0971-3026.125583
|View full text |Cite
|
Sign up to set email alerts
|

Horse-shoe lung-rediscovered via volume rendered images

Abstract: Horseshoe lung, usually associated with pulmonary venolobar syndrome, is a rare congenital anomaly involving the fusion of the postero-basal segments of the right and left lungs across the midline. The fused segment or the isthmus lies posterior to the pericardium and anterior to the aorta. The associated pulmonary venolobar syndrome involves anomalous systemic arterial supply and anomlaous systemic venous drainage of the right lung. With the advent of MDCT imaging, we can diagnose this rare condition as well … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 7 publications
0
11
0
Order By: Relevance
“…Patients with horseshoe lung may be asymptomatic; however, patients may also present with respiratory symptoms, including respiratory distress, pneumonia, recurrent pulmonary infection, or symptoms of pulmonary hypertension [ 3 , 13 ], although these symptoms are nonspecific. Most patients are diagnosed below the age of 1 year [ 14 ]. For the diagnosis of horseshoe lung, CT represents a useful imaging technique [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with horseshoe lung may be asymptomatic; however, patients may also present with respiratory symptoms, including respiratory distress, pneumonia, recurrent pulmonary infection, or symptoms of pulmonary hypertension [ 3 , 13 ], although these symptoms are nonspecific. Most patients are diagnosed below the age of 1 year [ 14 ]. For the diagnosis of horseshoe lung, CT represents a useful imaging technique [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…The fusion of both lungs via a parenchymal isthmus can be easily detected on CT images [ 6 ]. The pleural line may appear as a thin fibrous band in the parenchymal isthmus [ 14 ]. Angiography and bronchography revealed that the bronchial and arterial branches that supply the isthmus arise from the hypoplastic lung [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, there are a few reported cases of bilateral scimitar syndrome with horseshoe lung 11 16 17. The scimitar veins are commonly multiple, and these drain the supradiaphragmatic IVC in horseshoe lung associated with scimitar syndrome in childhood 11 18 19. In a study of 16 patients diagnosed with scimitar syndrome, the scimitar vein drained to the infradiaphragmatic IVC in 10 patients, but the majority of the patients were adult and none of them had horseshoe lung 20.…”
Section: Discussionmentioning
confidence: 99%
“…Eighty percent of horseshoe lung cases are associated with scimitar syndrome, also known as the congenital pulmonary venolobar syndrome. [ 6 7 8 ] Association with other cardiovascular abnormalities, such as atrial septal defect, interventricular septal defect, persistent arteriosus ductus, and single left ventricle, may occur. [ 9 ] In patients with horseshoe lung, tracheal and bronchial stenosis and anomalous bronchial bifurcation are also reported.…”
mentioning
confidence: 99%
“…These anomalies needed confirmation in the past with invasive angiography or bronchography, but with the advent of multidetector CT (MDCT), the need for invasive imaging may be completely obviated and VR images would be sufficient to depict the complex anatomy much more clearly than the conventional imaging techniques. [ 7 ]…”
mentioning
confidence: 99%